Herd‐level prevalence of Salmonella Dublin among New York dairy farms based on antibody testing of bulk tank milk. (14th September 2018) - Cummings, Kevin J.; Virkler, Paul D.; Wagner, Bettina; Lussier, Elizabeth A.; Thompson, Belinda S.
Abstract: Salmonella Dublin is an important cause of salmonellosis among dairy cattle and poses a considerable threat to public health. This serotype is increasingly being identified among bovine Salmonella isolates from clinical samples in the north‐eastern United States, and these isolates are generally multidrug resistant. Our objective was to estimate the herd‐level prevalence of Salmonella Dublin among dairy cattle herds throughout New York. Bulk tank milk samples from nearly all commercial dairy herds in New York were collected from milk quality testing laboratories during the first half of 2013. Antibody testing of bulk tank milk was performed using a Salmonella Dublin ELISA kit. Samples representing 4, 896 commercial dairies were collected, and antibodies against Salmonella Dublin were detected in 46 herds (0.9%; 95% CI, 0.7%–1.3%). Given the herd‐level sensitivity of ELISA testing for Salmonella Dublin in bulk tank milk at a single timepoint, this approach presumably underestimated the true prevalence. Some Salmonella Dublin‐positive herds had both positive and negative bulk tanks at the same sampling time, indicating that herds with multiple tanks should test all of them when using this ELISA. Further research is needed to better understand the epidemiologic features of Salmonella Dublin in the north‐eastern United States, including risk factors for introduction into dairy herds and principal transmission pathways.